2022
DOI: 10.1093/brain/awac049
|View full text |Cite
|
Sign up to set email alerts
|

ActivatingRAC1variants in the switch II region cause a developmental syndrome and alter neuronal morphology

Abstract: RAC1 is a highly conserved Rho GTPase critical for several cellular and developmental processes. De novo missense RAC1 variants cause a highly variable neurodevelopmental disorder. Some of these variants have been previously shown to have a dominant negative effect. Most previously reported patients with this disorder have either severe microcephaly or severe macrocephaly. Here we describe eight patients with pathogenic missense RAC1 variants affecting residues between Q61 and R68 within the swi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The structural modeling studies also support our hypothesis that the p.Tyr40His variant inactivates RAC3-PAK1 signaling. Previous functional analyses of variants in the Switch II region showed constitutive activation of downstream signals in the RAC1-PAK1 axis 14 , and that variants adjacent to and in the Switch I region (p.Tyr40His and p.Asn39Ser) inactivate the signal. p.Tyr40His appeared to affect RAC3-PAK1 binding more strongly than p.Asn39Ser from the molecular modelling (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The structural modeling studies also support our hypothesis that the p.Tyr40His variant inactivates RAC3-PAK1 signaling. Previous functional analyses of variants in the Switch II region showed constitutive activation of downstream signals in the RAC1-PAK1 axis 14 , and that variants adjacent to and in the Switch I region (p.Tyr40His and p.Asn39Ser) inactivate the signal. p.Tyr40His appeared to affect RAC3-PAK1 binding more strongly than p.Asn39Ser from the molecular modelling (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…All previously reported cases with RAC1 variants located in Switch I or II regions involved altered GTP/GDP-bound states 13 , 14 , 23 . In the Online Mendelian Inheritance in Man ( https://omim.org/ ), de novo RAC1 variants have been found in intellectual developmental disorder (MIM#617751) with the highly variable phenotype, such as neurodevelopmental delay with abnormal brain magnetic resonance imaging findings, epilepsy, facial dysmorphisms, cardiovascular malformations and poor feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo, heterozygous variants in RAC1 are associated with a distinct NDD that includes dysmorphic features, moderate/severe intellectual disability, seizures, hypotonia, CNS anomalies including cerebellar dysplasia, hypoplasia of the corpus callosum, enlarged ventricles, mega cisterna magna, a thin brainstem, white matter abnormalities, and polymicrogyria [41,55]. In a study, 14 cases with de novo, heterozygous RAC1 mutations were reported [41,55]. Of the six cases that had functional studies, four were shown to be gain-of-function type and two had a dominant-negative effect.…”
Section: Disease Phenotypes Associated With Deficient Functioning Of ...mentioning
confidence: 99%
“…Dysregulation of Rac1 leads to abnormalities in synaptogenesis (Wiens et al, 2005), spine morphology (Nakayama et al, 2000), and synaptic plasticity (Haditsch et al, 2009), each of which has been proposed to be a contributing factor for various developmental brain disorders, including autism spectrum disorder (ASD) and schizophrenia. For example, altered Rac1 activity is a factor in ASD-like behaviors in the DOCK4-deficient mouse model of ASD (Guo et al, 2021), and a mutation in the switch II region of RAC1 is implicated in neurodevelopmental disorders (Banka et al, 2022). Additionally, mutations in the Rac-GEF Trio are associated with autism and intellectual ability and impair neuroligin-1 induced synaptogenesis (Fingleton & Roche, 2023; Tian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%